The Contribution of Abu-Hamid al-‎Ghazali to Shaping Businesspeople's ‎Personalities - Arif Zunaidi (Universitas Darussalam Gontor, 2022)
As a Sufi figure, al-Ghazali developed moral Sufism as part of his desire to provide ethics in dealing with worldly activities so that they are more focused and run. This study is structured in the form of a library research project based on a character's thoughts at a specific time. This study also employs a descriptive technique approach, which is a type of study that describes existing phenomena. This method was chosen because the goal of this research was to provide an in-depth picture of the subject of the study, namely how the process of the concept of akhlaqi Sufism should be and its relevance to business actors according to Imam Al-Ghazali. Sufism al-akhlaqi Ghazali teaches Tawhid, which holds a significant position in Islamic business ethics, according to his research findings. Every Muslim is born with two consciences as a result of this monotheism. First and foremost, everyone must recognize that this nature was created by Allah SWT for the benefit of humans and that Allah is the sole owner. All natural resources, or factors of production in economic parlance, are Allah SWT's absolute property. Human ownership, on the other hand, is a relative concept. Second, humans were created in this world to serve God, and any worship performed by humans will be considered worship. Internalization of these two perspectives will have an impact on Muslim commercial activities. Every business owner must recognize that their work is also an act of worship to Allah SWT.